External stressors and trajectories of marital quality during the early years of Chinese marriage: Buffering effects of resources at multiple ecological levels. (May 2022) - Li, Xiaomin; Curran, Melissa A.; Butler, Emily; Toomey, Russell B.; Cao, Hongjian; Fang, Xiaoyi
Drawing from the stress resistance process within the conservation of resources theory, this study examined how resources at multiple ecological levels—personal (self-esteem), relational (spousal support), and social network (relationships with parents and parents-in-law)—moderate the spillover and crossover effects from external stressors to trajectories of marital quality. We used three-annual-wave, dyadic data from 268 heterosexual Chinese couples who were at the beginning stages of marriage. Consistent with theory, personal, relational, and social network resources all buffered the detrimental effects of external stressors for marital quality. Further, nuanced findings emerged, likely given the social cultural context in contemporary China. Specifically, gender differences emerged in whether a specific resource attenuated the detrimental effects of external stressors (e.g., husbands' vs. wives' self-esteem attenuated detrimental effects of external stressors). Moreover, opposite patterns existed for the short-term versus long-term results for husbands' relational resources. In sum, our findings highlight that when helping couples cope with stressors, it is necessary to (a) include available resources at multiple ecological levels (personal, relational, social network) and (b) consider whether social cultural backgrounds may have influenced the effectiveness of a specific resource.